Developing Realistic and Child-friendly Learning Model for Teaching Mathematics - Nining Setyaningsih; Sri Rejeki; Naufal Ishartono (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2019)
This study aims to develop a learning model based on the theory of realistic mathematics education and child-friendly learning for teaching mathematics in junior high school. This research is conducted using Plomp’s educational design research that consists of four development phases: 1) preliminary investigation, 2) designing, 3) realization, and 4) revision, evaluation. In addition, this study also tests the mathematics instructional model prototype being developed and validated by an expert. Based on the analysis, it can be concluded that: 1) the teacher’s learning management in the implementation of realistic and child-friendly learning model can be classified “very good”, 2) the prototype model is categorized “very good” in improving students’ activities , and 3) the students’ responses toward the developed mathematics instructional model are